Intercultural Assessment Through Peircean Signs of Scholars’ Digital Divide - Harmayanthi, V Y (KnE Social Sciences, 2018)
Individuals using advanced technology appear to react differently when explaining their understanding when exposed to information and communication technology tools and access, such as computers, mobile phones, and the Internet. This creates a digital divide among scholars in regard to the ability to access modern information and communication technology. Intercultural competence is the key element of their ability to select appropriate creative materials in education subjects and specified areas effectively. A particular way of assessing that competence needs to be applied to keep scholars in a globally harmonized system between indigenous and foreign cultures. This study was a qualitative research and used Peircean signs to construct clarity as a way of assessing intercultural competence in the scholarly digital divide. The objective of this research was to find out deeply the effectual way of Peircean signs as assessment in intercultural competence. The data were collected from 20 scholars’ ICT materials. Their creation was based on their experiences when carrying out community service activities in the Putri mountain area, Bogor West Java, in 2017. The results show the difference assessment in cultural containers. They are separated into 1) iconic signs; 2) indexical signs, and 3) symbolic signs of the indigenous and foreign cultures that reflect the intercultural competence. Keywords: digital divide, intercultural assessment, Peircean signs